Oxidative stability of sacha inchi oils (Plukenetia Huayllabambana and Plukenetia Volubilis) and their importance in the food industry - Chasquibol, Nancy (2020)
This work aims to determine the oxidative stability of sacha inchi oils(Plukenetia huayllabambana and Plukenetia volubilis), both non-microencapsulated and microencapsulated with different wall materials, using the Rancimat method at 70, 80, 90 and 100 oC, and the linear extrapolation technique based on induction periods. Shelf-life values were estimated ​​at 25 °C. The following physical and chemical analysis were carried out: acidity level, peroxide index, oxidative stability and humidity.